Association of early left ventricular dysfunction with advanced magnetic resonance white matter and gray matter brain measures: The CARDIA study. Issue 11 (8th November 2017) - Armstrong, Anderson C.; Muller, Majon; Ambale‐Ventakesh, Bharath; Halstead, Michael; Kishi, Satoru; Bryan, Nick; Sidney, Stephen; Correia, Luís C. L.; Gidding, Samuel S.; Launer, Lenore J.; Lima, João A. C.
Abstract : Introduction: Relations between heart failure and clinically manifested stroke are well known, but the associations between heart and brain early abnormalities are not totally clear. Aims: We explore relations of subclinical brain abnormalities with early cardiac dysfunction in a large healthy middle‐aged biracial cohort. Methods: The CARDIA study enrolled 5115 young adults aged 18–30 years at baseline (1985–1986). We assessed 719 Caucasian and African American participants of the CARDIA study, with echocardiograms and brain MRI at follow‐up year 25 (2010–2011). Echocardiography assessed aortic root diameter; LVEF; circumferential, longitudinal, and radial deformation. Cerebral MRI DTI, and, on a subset, ASL perfusion sequences were used to assess white matter fractional anisotropy and gray matter cerebral blood flow (CBF). Linear regression explored relations between cardiac parameters and cerebral measures, adjusting for anthropometrics, risk factors, and brain constitutional variation. Results: Mean age 50 ± 4 years, SBP 118 ± 15 mm Hg; 60% white, and 48% men. Mean CBF was 46 ± 9 mL/100 g/min, and white matter fractional anisotropy was 0.31 ± 0.02. Worse circumferential deformation and larger aortic root were related to worse white matter fractional anisotropy. Worse radial systolic deformation was related to worse CBF in multivariable models. LVEF did not relate to early brain abnormalities. Conclusions: In spite of no apparent effect of LV ejection fraction, early subclinical cardiac dysfunction and brain abnormalities are present and associated in middle‐aged generally healthy individuals.